Personality, Movement, andInfection in a Wild Population of Bank Voles (Myodes glareolus) - Erixon, Filippa (2021)
Personality affects many life decisions and potentially has major consequences on ecological and evolutionary processes. Personality-dependent local movement affects interactions between individuals, resource acquisition, and the risk of encountering predators and pathogens. Thus, differences in behavioral types can have larger consequences on fitness. Here, I investigated personality-dependent local movement, Puumala (PUUV) infection, and overwintering survival of a wild population of bank voles (Myodes glarolus). Voles were captured and tagged in a field site in Northeastern Sweden. I evaluated personality using standardized tests in field, collected mouth swab samples for PUUV analysis, and recorded local movement using an automated technology for logging PIT-tagged voles. Anxiety- and stress-tolerant voles visit the human dwellings more than the forest and thus exhibit a habitat preference. Moreover, the stress and anxiety-tolerant voles occupying the human dwelling to a larger degree were temporally closer to each other posing a potential risk for encountering pathogens. However, no PUUV was detected, indicating that infection risk was low and that neither of the habitats act as an infection hub or refugia during the study period. Furthermore, overwintering survival showed tendencies of being positively affected by anxiety- and stress-tolerance. However, the mechanisms behind this remain undetermined. Consequently, this pilot study provides evidence for personality-dependent local movements and provides a compelling argument for further long-term studies of the interaction between personality-dependent movement and ecological factors as well as their effect on survival.